2023
DOI: 10.1063/5.0158003
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of a characteristic airfoil at low-Reynolds number and transonic flow under Mars sand-containing environment

Abstract: The propeller tip of an unmanned aerial vehicle on Mars operates at a low-Reynolds number (Re = 1–5 × 104) and transonic velocity range (Ma = 0.7–1.2). Generally, this implies flow separation and shock waves in the flow field. Furthermore, the impact of Martian atmospheric sand particles significantly affects the aerodynamic performance, and numerical simulations of this issue have received increasing attention recently. Aimed at a characteristic airfoil, the study of a low-Reynolds number transonic flow and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, due to the spatial constraints of rotary-wing Mars UAVs, it is often necessary to employ control strategies specifically tailored to coaxial rotary-wing Mars UAVs. This presents distinctions from conventional quadcopter control methods [98,99]. This is essential to ensure the successful execution of UAV exploration missions on Mars.…”
Section: Research On Control Methods Of Rotary-wing Mars Uavsmentioning
confidence: 99%
“…Furthermore, due to the spatial constraints of rotary-wing Mars UAVs, it is often necessary to employ control strategies specifically tailored to coaxial rotary-wing Mars UAVs. This presents distinctions from conventional quadcopter control methods [98,99]. This is essential to ensure the successful execution of UAV exploration missions on Mars.…”
Section: Research On Control Methods Of Rotary-wing Mars Uavsmentioning
confidence: 99%
“…Hasan (Hasan et al , 2022b; Hasan and P, 2022a) studied the influence of supercritical airfoil on helicopter characteristics and found that supercritical airfoil can increase efficiency and produce good aerodynamic characteristics. Liu (Liu et al , 2023) analysed the effect of sandy flow with a low Reynolds number in transonic flow on the aerodynamic performance of an airfoil of a Mars UAV.…”
Section: Introductionmentioning
confidence: 99%